THE URGENCY TO IDENTIFY LOW MUSCLE MASS AMONG ELDERLY: COMMUNITY SERVICE IN NURSING HOME - Farapti Farapti; Chusnul Fadilla; Amelliya Nur Heriyana; Afifah Nurma Sari; Sri Adiningsih (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2022)
Introduction: Decreased muscle mass in the elderly often occurs due to the aging process. Identification of muscle mass needs to be done to optimize the health status of the elderly. So, this article will identify muscle mass in the elderly. Methods: Community service was carried out to 54 elderly people in a nursing home. For the elderly, health checks are carried out including body composition measurements, especially muscle mass, as well as nutrition education and counseling. The inclusion criteria for the elderly who take part in the activity include (1) healthy and able to stand; (2) fully aware; (3) not bed rest; (4) able to communicate and cooperative. The data presented include age, length of stay, body mass index, and body composition, namely muscle mass. Results: About three-quarters of the elderly are women and have lived in a nursing home for approximately 3 years. The average nutritional status of the elderly is normal (21.6 ± 4.5 kg/m2). As many as 96.3% of the elderly have a low muscle mass index and 53.7% of the elderly have a high fat mass. The muscle mass of older men was higher than that of women (26.2 ± 2.8 vs 21.9 ± 1.9). Conclusion: Almost all the elderly has low muscle mass due to the physiological aging process and decreased activity of the elderly in using muscles. . Elderly women were observed to have lower muscle mass index than that of men. Identification of muscle mass strength is also needed to find out more about sarcopenia in the elderly.